2004
DOI: 10.1016/j.materresbull.2004.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis, characterization and magnetic properties of NaVGe2O6 and LiVGe2O6

Abstract: Supercritical fluids are shown to be an excellent reaction media for the synthesis of novel solid state phases at intermediate temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…In contrast to NaVGe 2 O 6 , there is no striking disagreement about the crystal structure of LiVGe 2 O 6 in Ref. 4,24. However, we were not able to reproduce distances presented in Ref.…”
Section: Computational Detailscontrasting
confidence: 61%
See 2 more Smart Citations
“…In contrast to NaVGe 2 O 6 , there is no striking disagreement about the crystal structure of LiVGe 2 O 6 in Ref. 4,24. However, we were not able to reproduce distances presented in Ref.…”
Section: Computational Detailscontrasting
confidence: 61%
“…However, we were not able to reproduce distances presented in Ref. 24 from their crystal structure. Therefore, the study of electronic and magnetic properties of both NaVGe 2 O 6 and LiVGe 2 O 6 was postponed for the future, when all the problems about the crystal structure of these compounds would be resolved.…”
Section: Computational Detailsmentioning
confidence: 94%
See 1 more Smart Citation
“…from P2 1 /c to C2/c, to higher temperatures or lower pressures, as demonstrated, for example, for LiFeGe 2 O 6 (Redhammer et al, 2010;Nestola et al, 2009). For the NaM 3+ Ge 2 O 6 system, the structures of NaFeGe 2 O 6 (Redhammer et al, 2011), NaCrGe 2 O 6 (Redhammer, Roth, Topa & Amthauer, 2008;Nenert et al, 2009), NaVGe 2 O 6 (Emirdag-Eanes & Kolis, 2004), NaMnGe 2 O 6 (synthesized at high pressure; Chen et al, 2013) and NaScGe 2 O 6 (Genkina et al, 1985) have been reported. For the latter compound, only isotropic atomic displacement parameters were given.…”
Section: Introductionmentioning
confidence: 75%
“…Structural parameters of SrMn(VO 4 )(OH) at 300 K (s.g. P2 1 2 1 2 1 (no 19),. Z= 4, a = 6.1322(13) Å, b = 7.7201(19) Å, c = 9.414(2) Å; R1 = 0.0175, wR2 = 0.0405; Flack x = -0.010(6))…”
mentioning
confidence: 99%